2020
DOI: 10.1177/0956797620903717
|View full text |Cite
|
Sign up to set email alerts
|

Achieving More With Less: Intuitive Correction in Selection

Abstract: Choosing between candidates for a position can be tricky, especially when the selection test is affected by irrelevant characteristics (e.g., reading speed). One can correct for this irrelevant attribute by penalizing individuals who have unjustifiably benefited from it. Statistical models do so by including the irrelevant attribute as a suppressor variable, but can people do the same without the help of a model? In three experiments (total N = 357), participants had to choose between two candidates, one of wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…The results of Experiments 1 and 2 show that providing advice led to participants' selections being more similar to what a normative model recommends. Approximately 60% of the participants (in both studies) chose normatively when presented with advice, compared to less than 20% who did so without advice (in line with the results of Rabinovitch et al, 2020). We found this effect regardless of whether the participants had already committed to a decision or not.…”
Section: Discussion Of Experiments 1 Andsupporting
confidence: 84%
See 3 more Smart Citations
“…The results of Experiments 1 and 2 show that providing advice led to participants' selections being more similar to what a normative model recommends. Approximately 60% of the participants (in both studies) chose normatively when presented with advice, compared to less than 20% who did so without advice (in line with the results of Rabinovitch et al, 2020). We found this effect regardless of whether the participants had already committed to a decision or not.…”
Section: Discussion Of Experiments 1 Andsupporting
confidence: 84%
“…To overcome this bias, DMs need to adjust their evaluations of the candidates accordingly. Algorithms such as statistical models can perform this correction, but Rabinovitch et al (2020Rabinovitch et al ( , 2022 demonstrated that people struggle to do it intuitively. Therefore, we examined how willing would DMs be to be advised and assisted by external sources and whether they treat advice from human experts or algorithms differently in this context.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been well documented that people in charge of candidate selection decisions such as hiring or university admission decisions are swayed by features of applicants that are not directly related to job performance. Examples include height (Harper, 2000), physical attractiveness (Hamermesh, 2011), gender (Marlowe et al, 1996), and performance on unrelated tasks (even when explicitly informed that the task is unrelated; Rabinovitch et al, 2020). Most pertinent, recruiters seem to match applicants to certain jobs or careers based on mere stereotypes of the applicant and on the degree to which these stereotypes “fit” the job description, discounting the applicant’s actual capabilities and character.…”
Section: Impression Formation From Nonverbal Cuesmentioning
confidence: 99%